Effect of cooperative learning model type of group investigation and adversity quotient of students on mastery of chemical concepts on salt hydrolysis material - Havizhah Havizhah; Muhaimin Muhaimin; Damris Muhammad (Pascasarjana Universitas Negeri Medan, 2020)
This study aims to see the effect of the cooperative learning model type of group investigation and adversity quotient of students on the mastery of chemical concepts on salt hydrolysis. This research is a quasi-experimental research with a control group posttest only design using a 2 × 3 factorial design. The research was conducted in class IX MIA SMA N 10 Batanghari with two classes. Sampling was done by total sampling. Data collection techniques are questionnaires, tests and documentation. The test instrument was used to determine the value of mastery of chemical concepts on salt hydrolysis. Meanwhile, the questionnaire instrument was used to determine the level of adversity quotient of students. Data processing used two-way ANOVA. The results showed that the cooperative learning model group Investigation type and the adversitiy quotient of the climber type students had high mastery of chemical concepts, but there was no interaction between the group investigation type learning model and the adversity quotient on the mastery of chemical concepts on salt hydrolysis due to the learning model and adversity quotient influence on mastery of chemical concepts independently. Based on the results of the study, it can be concluded: (1) there is an effect of the group investigation type cooperative learning model on the mastery of chemical concepts (2) there is an effect of students adversity quotient on chemical concept mastery (3) there is no interaction between the cooperative learning model group investigation type with students' adversity quotient on mastery of chemical concepts in salt hydrolysis.Keywords: Cooperative learning model type of group investigation (GI), Adversity quotient (AQ), Mastery of chemical concepts, Salt hydrolysis